Willingness to Pay for Conservation of Wiang Kum Kam Cultural Heritage - Sukchitpinyo, Khodchaporn; Chokethaworn, Kanchana (WMS Journal of Management, 2016)
Wiang Kum Kam, an important cultural heritage of Chiang Mai, confronts with flooding problem every year in rainy season. Especially in 2011, it was damaged from flooding severely. In order to conserve Wiang Kum Kam, the objective of this study is to assess tourists’ willingness to pay for remediation and protection against flooding in Wiang Kum Kam. The results represent conservative attitude of people towards the cultural heritage for next generation. Open-ended CVM questionnaires are used to collect data, and the Tobit model is then used to analyze their willingness to pay for remediation with maximum likelihood estimation as well as other influencing factors from the samples: 400 Thai tourists who visited Wiang Kum Kam. By using accidental random sampling, it is found that Thai tourists who visited Wiang Kum Kam have willingness to pay 149.52 Baht/ person per times to revive Wiang Kum Kam, an economic value of conservation is 3,692,695.44 Baht per year. Factors influencing their willingness to pay were income, expenses, education, occupation and satisfaction of tourists. The average level of tourist’s satisfaction is medium. Tourists mention that signs, landscape, maintenance, interesting activities and safety should be improved to impress tourists. The information from this study can be used to support in making policies and allocating budget for development and conservation of Wiang Kum Kam.